Phenotypic and genotypic analysis of Borrelia burgdorferi isolates from various sources. - Adam, T (1991)
A total of 17 B. burgdorferi isolates from various sources were characterized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis of whole-cell proteins, restriction enzyme analysis, Southern hybridization with probes complementary to unique regions of evolutionarily conserved genes (16S rRNA and fla), and direct sequencing of in vitro polymerase chain reaction-amplified fragments of the 16S rRNA gene. Three groups were distinguished on the basis of phenotypic and genotypic traits, the latter traced to the nucleotide sequence level.